Bio-based rhamnolipids production and recovery from waste streams: Status and perspectives. (January 2021) - Varjani, Sunita; Rakholiya, Parita; Yong Ng, How; Taherzadeh, Mohammad J.; Hao Ngo, Huu; Chang, Jo-Shu; Wong, Jonathan W.C.; You, Siming; Teixeira, Jose A.; Bui, Xuan-Thanh
Graphical abstract: Highlights: Rhamnolipid can be recovered from waste streams. The major stumbling block in rhamnolipid production is cost of production. Various applications of Rhamnolipid have been explained. Summarised opportunities for research innovations in bio-based rhamnolipids field. Abstract: Bio-based rhamnolipid production from waste streams is gaining momentum nowadays because of increasing market demand, huge range of applications and its economic and environment friendly nature. Rhamnolipid type biosurfactants are produced by microorganisms as secondary metabolites and have been used to reduce surface/interfacial tension between two different phases. Biosurfactants have been reported to be used as an alternative to chemical surfactants. Pseudomonas sp. has been frequently used for production of rhamnolipid. Various wastes can be used in production of rhamnolipid. Rhamnolipids are widely used in various industrial applications. The present review provides information about structure and nature of rhamnolipid, production using different waste materials and scale-up of rhamnolipid production. It also provides comprehensive literature on various industrial applications along with perspectives and challenges in this research area.